Public awareness of home accident risks–some implications for health promotion. Issue 2 (June 1992) - Bryce, G; Fakher, N
Abstract : Through daily contact with injured people there was a feeling that most people are sufficiently aware of the dangers in specific risk factor activities, but were not fully aware that they could do a lot to prevent harm coming upon themselves. This paper describes the results of a self-administered questionnaire about the accidents people suffered at home, their level of awareness of the risk they were undertaking, whether they had had a similar accident before, what they think the recovery period from their injury is likely to be and knowledge of, and accidents involving, 17 generally known risk activities. The results confirm that most people are indeed aware of dangers yet a large number still have accidents in spite of that. The results also indicate that campaigns advising people how to avoid these dangers could be successful.